Whole-Genome Based Molecular Characterization of Multi-Drug Resistant Enterobacter cloacae Complex and klebsiella aerogenes Isolated from Lebanon - Amayri, Sara (2020)
Enterobacter cloacae complex (ECC) and Klebsiella aerogenes, are Gram-negative nosocomial pathogens linked to different types of infections. The emergence of resistance to carbapenems, last treatment resort for multi-drug-resistant bacterial infections, led to the increased interest in carbapenem-resistant organisms. In this study, we performed whole-genome sequencing of 44 clinical ECC and K. aerogenes isolates collected during 2013-2018 from Lebanon. Their antimicrobial susceptibility profiles were determined by MICs using the Vitek2 automated system. We also used hsp60 genotyping and average nucleotide identity (ANI) comparison to better identify at the species and subspecies level with the ECC isolates. Pulse field gel electrophoresis, multilocus sequence typing (MLST) and whole genome-based SNPs analysis were performed to study the genetic relatedness within the studied isolates. The whole-genome sequencing (WGS) provided enough data to perform in silico multilocus sequence analysis (MLST), detection of resistance determinants, and plasmid annotation. Our results revealed that 88.6% (n=39) of the isolates belonged to the E. hormaechei species with E. hormaechei subsp. xiangfangensis being the dominant subspecies (54.54%; n=24), while 11.4% (n=5) were identified as K. aerogenes. Only 16% (n=7) of the isolates were susceptible to carbapenems. ST114 (33%; n=13) and ST182 (13%; n=5) were the two most common identified STs in the ECC population. blaNDM-1 was the major carbapenemase encoding gene detected in 59% (n=23) of the carbapenem resistant isolates and was associated with a 104.4 Kb IncFII plasmid. blaOXA-48 was identified in three of the CR isolates (7.7%) on a 61.9 Kb IncL replicon, whereas its variant blaOXA-181 was detected in 13% (n=5) of CR isolates being exclusively disseminated through a 51.3 Kb IncX3 plasmid. This study revealed the incidence, diversity, dissemination and antimicrobial resistance patterns and evolution of the carbapenem resistant Enterobacter spp. Recovered from Lebanon. Our findings could help in understanding resistance profiles, genomic structure and environment as well as cross-transmission of carbapenem resistant ECC and K. aerogenes isolates in Lebanon and the MENA region.